Analisis Kesalahan Siswa SMP pada Penyelesaian Masalah Sistem Persamaan Linear Dua Variabel - Anna Citra Islamiyah; Sudi Prayitno; Amrullah Amrullah (Didaktik Matematika, 2018)
Background of this research is many student errors at solving linear equation systems with two variables problems. The research aim is to know the kinds and level of errors at solving linear equation systems with two variables problems. This research is descriptive quantitative. The subject of this study is 30 students grade 7 from one of junior high school at Mataram, West Nusa Tenggara. A data collection done by tested and interviewed. The error of the problem solving that could analyze were a reading error, comprehension, transformation, process skills and encoding. Result of the research indicate that percentage of reading error was 17.78% (too low category), comprehension error was 55.56% (middle category), transformation error was 18.52% (too low category), process skills error was 36.67% (low category) and encoding error was 83.70% (too high category).